2510. Epidemiological Change of Cytomegalovirus Diseases in the Developed Country With High Cytomegalovirus–Seropositive Rate: Nationwide, Whole Population-Based Study. (26th November 2018) - Yoo, Seul Gi; Han, Kyung Do; Lee, Kyoung Hwa; Lim, Joo Hee; La, Yeonju; Kwon, Da Eun; Han, Sang Hoon; Song, Young Goo
Abstract: Background: The cytomegalovirus (CMV) can cause tissue-invasive diseases in various organs through primary infection or reactivation of latent status over a lifetime. Even though individuals with risk of CMV diseases such as elderly or immunocompromised patients are constantly increasing, the recent epidemiologic change of it is not fully evaluated, especially on a grand scale. Methods: We used the Korean Health Insurance Review and Assessment Service (HIRA) claim nationwide database of about 50 million individuals, nearly entire population, between 2010 and 2015. The South Korean National Health Insurance Service operates the "Relieved Co-payment Policy" program as out-of-pocket relief in patients with rare intractable diseases including CMV. The unique code of CMV end-organ diseases in the program is completely matched with ICD-10 B25 except congenital CMV infection and mononucleosis. By this process, the cohort of CMV diseases was established from the HIRA data warehouse. The 628 case (with CMV) and 3, 140 control (without CMV disease) group matched with age and sex were selected in same dataset to evaluate the effect of CMV diseases on all-cause death. Results: The standardized prevalence rates of CMV diseases adjusted with age and sex have continuously increased from 0.55/100, 000 in 2010 to 1.41/100, 000 individuals in 2015. The crude prevalence was the highest in youngest group of less than 9-year-old every year for 6 years (4.34/100, 000 in 2015) and second highest in individuals with 60–69-year-old (2.28/100, 000 in 2015). Male population had the higher crude and standardized prevalence than female in all age groups every year. The individuals in lowest income status had the highest standardized prevalence (7.1/100, 000 in 2015). In model adjusted by age, sex, low income, diabetes, hypertension and dyslipidemia, case group had 4.8 of hazard ratio (95% CI, 3.3–7.0) to all-cause of death compared with control group. The Kaplan–Meier survival curve revealed the significantly higher rate of all-cause mortality in case group ( P < 0.001). Conclusion: The occurrence of CMV disease is steadily on rise during the past 6 years in nationwide data, especially in male infant and childhood as well as elderly individuals, with association of high mortality. Disclosures: All authors: No reported disclosures.